Methods for large-scale image-based localization using structure-from-motion point clouds - Cheng, Wentao (Nanyang Technological University, 2020)
Image-based localization, i.e. estimating the camera pose of an image, is a fundamental task in many 3D computer vision applications. For instance, visual navigation for self-driving cars and robots, mixed reality and augmented reality all rely on this essential task. Due to easy availability and richness of information, large-scale 3D point clouds reconstructed from images via Structure-from-Motion (SfM) techniques have received broad attention in the area of image-based localization. Therein, the 6-DOF camera pose can be computed from 2D-3D matches established between a query image and an SfM point cloud. During the last decade, to handle large-scale SfM point clouds, many image-based localization methods have been proposed, in which significant improvements have been achieved in many aspects. Yet, it remains difficult but meaningful to build a system, which (i) robustly handles the prohibitively expensive memory consumption brought by large-scale SfM point clouds, (ii) well resolves the match disambiguation problem, i.e. distinguishing correct matches from wrong ones, which is even more challenging in urban scenes or under binary feature representation and (iii) achieves high localization accuracy so that the system can be safely applied in low false tolerance applications such as autonomous driving. In this thesis, we propose three methods that tackle these challenging problems to make a further step towards such an ultimate system. First of all, we aim to solve the memory consumption problem by means of simplifying a large-scale SfM point cloud to a small but highly informative subset. To this end, we propose a data-driven SfM point cloud simplification framework, which allows us to automatically predict a suitable parameter setting by exploiting the intrinsic visibility information. In addition, we introduce a weight function into the standard greedy SfM point cloud simplification algorithm, so that more essential 3D points can be well preserved. We experimentally evaluate the proposed framework on real-world large-scale datasets, and show the robustness of parameter prediction. The simplified SfM point clouds generated by our framework achieve better localization performance, which demonstrates the benefit of our framework for image-based localization in devices with limited memory resources. Second, we investigate the match disambiguation problem in large-scale SfM point clouds depicting urban environments. Due to feature space density and massive repetitive structures, this problem becomes challenging if solely depending on feature appearances. As such, we present a two-stage outlier filtering framework that leverages both the visibility and geometry information of SfM point clouds. We first propose a visibility-based outlier filter, which is based on the bipartite visibility graph, to filter outliers on a coarse level. By deriving a data-driven geometrical constraint for urban environments, we present a geometry-based outlier filter to generate a set of fine-grained matches. The proposed framework only relies on the intrinsic information of an SfM point cloud. It is thus widely applicable to be embedded into existing image-based localization approaches. Our framework is able to handle matches of very large outlier ratio and outperforms state-of-the-art image-based localization methods in terms of effectiveness. Last, we aim to build a general-purpose image-based localization system that simultaneously solves the memory consumption, match disambiguation and localization accuracy problems. We adopt a binary feature representation and propose a corresponding match disambiguation method by adequately utilizing the intrinsic feature, visibility and geometry information. The core idea is that we divide the challenging disambiguation task into two different tasks before deriving an auxiliary camera pose for final disambiguation. One task focuses on preserving potentially correct matches, while another focuses on obtaining high quality matches to facilitate subsequent more powerful disambiguation. Moreover, our system improves the localization accuracy by introducing a quality-aware spatial reconfiguration method and a principal focal length enhanced pose estimation method. Our experimental study confirms that the proposed system achieves superior localization accuracy using significantly smaller memory resources comparing with state-of-the-art methods.